Wildlife Consumption Dynamics: Unveiling Conduru Park in Southern Bahia, Brazil - Vicente dos Santos Teixeira, Joanison; Duarte da Rocha, Wesley; Silveira Miranda, Jefferson Eduardo; Schiavetti, Alexandre (Ethnobiology and Conservation, 2024)
The current investigation aimed to identify the wild animals utilized as a food source in five locations within the Serra do Conduru State Park region, Bahia, Brazil. The field survey was conducted from June 2016 to July 2017, involving semi-structured interviews and informal conversations with 45 hunters. The composition of species used for sustenance in the five locations was characterized through permutation multivariate analyses of variance. Generalized linear models were constructed to evaluate whether socio-demographic variables among hunters influenced the number of captured species. A total of 67 species (34 families and 22 orders) of hunting significance were documented in the region, with 41 being hunted for consumption. The most represented taxa were mammals (32), birds (21), reptiles (13), and amphibians (1). Dicotyles tajacu, Dasypus novemcinctus, and Cuniculus paca emerged as the most targeted species for food. Hunters who still reside within the conservation unit capture a greater number of wild animals. Older hunters and those with smaller family sizes hunt a broader range of species. The rifle and domestic dogs are the predominant techniques employed in the region. The findings underscore the persistence of illegal hunting practices in the Serra do Conduru State Park region. This emphasizes the necessity for measures directed at the conservation of hunted species, particularly those identified as being under some degree of threat in nature.